Solidarity Interrupted: Coffee, Cooperatives, and Certification Conflicts in Mexico and Nicaragua. Issue 3 (2nd July 2020) - Wilson, Bradley R.; Mutersbaugh, Tad
Abstract : Ethical commodity networks have been advanced as a means to promote cooperative development, engender more democratic forms of governance, promote environmental conservation, and redistribute a greater share of returns to farmers and workers. This essay draws upon long-term ethnographic research on the role of solidarity within two Mesoamerican coffee-producing cooperatives to understand the effects of certification regimes that undergird many ethical commodity networks today. The essay uses a labor-centric conception of solidarity to demonstrate that the pressures and demands created by certifications intended to generate more just outcomes can also strain existing solidarities that bind cooperatives together.